Phylogenetic patterns of trait and trait plasticity evolution: Insights from amphibian embryos. (1st March 2018) - Relyea, Rick A.; Stephens, Patrick R.; Barrow, Lisa N.; Blaustein, Andrew R.; Bradley, Paul W.; Buck, Julia C.; Chang, Ann; Collins, James P.; Crother, Brian; Earl, Julia; Gervasi, Stephanie S.; Hoverman, Jason T.; et al.
Abstract: Environmental variation favors the evolution of phenotypic plasticity. For many species, we understand the costs and benefits of different phenotypes, but we lack a broad understanding of how plastic traits evolve across large clades. Using identical experiments conducted across North America, we examined prey responses to predator cues. We quantified five life‐history traits and the magnitude of their plasticity for 23 amphibian species/populations (spanning three families and five genera) when exposed to no cues, crushed‐egg cues, and predatory crayfish cues. Embryonic responses varied considerably among species and phylogenetic signal was common among the traits, whereas phylogenetic signal was rare for trait plasticities. Among trait‐evolution models, the Ornstein–Uhlenbeck (OU) model provided the best fit or was essentially tied with Brownian motion. Using the best fitting model, evolutionary rates for plasticities were higher than traits for three life‐history traits and lower for two. These data suggest that the evolution of life‐history traits in amphibian embryos is more constrained by a species' position in the phylogeny than is the evolution of life history plasticities. The fact that an OU model of trait evolution was often a good fit to patterns of trait variation may indicate adaptive optima for traits and their plasticities.